COMBINED ANTIBIOTIC AND IMMUNOMODULATORY THERAPY IN COMPLICATED RESPIRATORY INFECTIONS: A SYSTEMATIC ANALYSIS OF CLINICAL EFFICACY AND MODERN APPROACHES (International journal of artificial intelligence, 2026)
The management of complicated respiratory infections remains a cornerstone of pediatric and adult pulmonology, particularly given the rising challenges of antibiotic resistance and post-viral immune dysfunction. This article explores the clinical utility of integrating immunomodulators with traditional antibiotic regimens to treat severe respiratory conditions. By analyzing modern therapeutic strategies proposed in 2025, the study evaluates how this dual approach mitigates inflammatory damage while ensuring bacterial clearance. The findings suggest that combined therapy significantly reduces the duration of clinical symptoms, such as persistent cough, and prevents the transition of acute infections into chronic states. This analysis provides a framework for clinicians to optimize treatment protocols through a more holistic immunological perspective.